ChemInform Abstract: N‐Heterocyclic Carbene—Copper‐Catalyzed Group‐, Site‐, and Enantioselective Allylic Substitution with a Readily Accessible Propargyl(pinacolato)boron Reagent: Utility in Stereoselective Synthesis and Mechanistic Attributes. Issue 2 (23rd December 2015) - Shi, Ying; Jung, Byunghyuck; Torker, Sebastian; Hoveyda, Amir H.
Abstract: The first examples of allylic substitution reaction of allyl diethylphosphates with propargylated (pinacolato)boron compounds (II) are reported to provide generally branched products.